ZÉLIA MARIA DA COSTA LUDWIG: RESILIENCE IN PHYSICS - Assis Faustino, Gustavo Augusto (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Zélia Maria Da Costa Ludwig was born on April 22, 1968, in the city of Ituiutaba, in the Minas Triangle. Daughter of a lathe worker and a housewife, she was encouraged by her father, used to leaf through electronic magazines reading about electronic components and how to assemble electrical circuits. In 1989, she graduated in Physics from the Pontifical Catholic University of São Paulo, did a master's degree at IPEN (Institute of Energy and Nuclear Research), at the University of São Paulo (USP), where she obtained her title in 1994. In her doctorate, she glimpsed the possibility of working with new materials, as well as changing their properties for specific applications. In 2000, he obtained his doctoral degree and, in 2002, he earned another undergraduate degree at the Institute of Physics at USP. In 2007, Zélia Ludwig entered the Federal University of Juiz de Fora as a visiting professor. Two years later, she became an effective teacher at the institution, where she works today.